Book of Scientific Research Achievements of Program Group P2-0118 Textile Chemistry and Advanced Textile Materials: P2-0118, 1st Annual Meeting 2024 - Kreže, Tatjana; Fras Zemljič, Lidija (2024)
The publication presents an overview of the research achievements of Program Group P2-0118 Textile chemistry and advanced textile materials from 2021 to 2023 in the field of development of smart and multifunctional textiles and composite materials as well as circular economy concepts. Members of the program group present their research innovations and progress achieved within the framework of the program group's activities.
Keywords: advanced textile materials; composites; nanotechnology; biotechnology; surface functionalization and modification; circular economy